Here's looking at Euclid from counting ants to games of chance, an awe-inspiring journey through the world of numbers - Bellos, Alex 1969- (Free Press, 2010)
Whether writing about how algebra solved Swedish traffic problems, visiting the Mental Calculation World Cup to disclose the secrets of lightning calculation, or exploring the links between pineapples and beautiful teeth, Bellos guides his readers into the world of mathematics while uncovering fascinating stories of mathematical achievement--from the breakthroughs of Euclid, the greatest mathematician of all time, to the creations of today's Zen master of origami.